Cognitive effects of chemotherapy: An integrative review. (October 2021) - Shaw, Carli; Baldwin, Adele; Anderson, Carina
Abstract: Purpose: An estimated 18.1 million new cancer cases (excluding nonmelanoma skin cancers) were diagnosed worldwide in 2020. Despite a rising incidence of cancers worldwide, in developed countries with strong healthcare systems, survival rates are improving as a result of early detection, improved treatments and survivorship care (World Health Organisation (WHO), 2021). Whilst living longer, cancer survivors are often living with side effects of treatment, including chemotherapy related cognitive impairment, often termed "chemobrain". Method: An integrative review of contemporary literature answering the research question how does chemotherapy affect cognitive function? was undertaken utilising three computerised databases CINAHL, Medline and PUBMED, between 2015 and 2021. Data was thematically analysed to identify themes within published literature. Results: Thematic analysis identified four broad themes within the literature regarding chemotherapy induced cognitive impairment. Identified themes included; cognition as part of a complex scenario, proof of existence and searching for the cause, learning to play the game and timing of cognitive impairment. Conclusions: Aggressive treatment with chemotherapy in the adjuvant setting has drastically improved the survival of cancer patients. Subsequent to aggressive treatments, side effects such as cognitive impairment have presented, which may persist in the long term. Despite the exact aetiology of chemotherapy induced cognitive impairment being largely unknown, the consequences of the condition are impacting cancer survivors and their quality of life. Highlights: Review of chemotherapy related cognitive impairment. Long term side effects of chemotherapy. Quality of life impacted by chemotherapy related cognitive impairment.